2001
DOI: 10.1152/ajpheart.2001.280.2.h738
|View full text |Cite
|
Sign up to set email alerts
|

Na+/H+ exchange inhibition reduces hypertrophy and heart failure after myocardial infarction in rats

Abstract: We investigated the effect of sodium/hydrogen exchange inhibition (NHE-1) on hypertrophy and heart failure after coronary artery ligation (CAL) in the rat. Animals were subjected to occlusion (or sham) of the left main coronary artery and immediately administered a control diet or one consisting of the NHE-1 inhibitor cariporide for 13-15 wk. Hearts were separated by small [30% of LV) infarcts. CAL depressed change in left ventricular increase in pressure over time (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
92
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(101 citation statements)
references
References 32 publications
5
92
0
3
Order By: Relevance
“…Accordingly, inhibition of NHE by its specific inhibitor cariporide has been demonstrated to "rescue" several models of cardiac hypertrophy in vivo. [111][112][113] Because NHE inhibition does not appear to be associated with adverse hemodynamic consequences, this approach is a potentially interesting antihypertrophic treatment option.…”
Section: Na/h Exchangermentioning
confidence: 99%
“…Accordingly, inhibition of NHE by its specific inhibitor cariporide has been demonstrated to "rescue" several models of cardiac hypertrophy in vivo. [111][112][113] Because NHE inhibition does not appear to be associated with adverse hemodynamic consequences, this approach is a potentially interesting antihypertrophic treatment option.…”
Section: Na/h Exchangermentioning
confidence: 99%
“…8,9 Activation of this exchanger in myocardial ischemia appears to be causally related to the calcium overload observed during ischemia, 10 and several studies have demonstrated protection from ischemic injury by NHE inhibition both in animal models of myocardial ischemia (MI) and in patients undergoing coronary interventions. [11][12][13] A protective effect of cariporide has recently been demonstrated in the setting of post-MI remodeling, 14 where protection could be demonstrated up to 3 months after MI.…”
Section: The Cardiac Namentioning
confidence: 99%
“…12,22 TGF␤ 1 binds to membrane receptors and transmits signals via mitogen-activated protein kinases (MAPK)-dependent and Smad-dependent pathways. 23 In postinfarcted myocardium, a condition in which NHE-1 inhibition proved to be beneficial, 3 Smad expression is elevated and normalized after Angiotensin II AT 1 blockade. 24,25 NHE-1 is a common downstream effector of various of these intracellular signaling mechanisms.…”
Section: Baseline and Cariporide-induced Changes In Sbp Lvw Lvw/bw mentioning
confidence: 99%
“…[2][3][4][5] The inhibition of NHE-1 reduces the hypertrophy of the surviving myocytes after myocardial infarction 3 and of the hearts of spontaneously hypertensive rats (SHR) 2 and mice overexpressing ␤ 1 -adrenergic receptors. 4 Taken together, these findings seem to indicate a key role of NHE activity in the development of myocardial hypertrophy.…”
mentioning
confidence: 99%